1996
DOI: 10.1021/jo960256g
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Calix[4]arenes and Resorcin[4]arenes for the Complexation of Steroids

Abstract: Receptor molecules with large cavities synthesized by the combination of building blocks that already possess a cavity, viz. calix[4]arenes and resorcin[4]arenes, are described. These receptor molecules are synthesized by reaction of one or two upper rim 1,2-difunctionalized calix[4]arene fragments oriented either endo or exo toward a cavitand unit. The endo:exo ratio depends on the substituents at the 3- and 4-positions of the calix[4]arenes. These novel receptor molecules complex steroids with association co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…[6][7][8] The saccharide and alkyl glycoside complexation of upper-rim unsubstituted resorcinarenes were earlier studied by Aoyama et al [9,10] They detected sugar complexes mainly from apolar organic solutions by using circular dichroism (CD) and 1 H NMR spectroscopic techniques. In their studies, the extraction of ribose from a polar protic solvent into an apolar aprotic solvent was even reported.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The saccharide and alkyl glycoside complexation of upper-rim unsubstituted resorcinarenes were earlier studied by Aoyama et al [9,10] They detected sugar complexes mainly from apolar organic solutions by using circular dichroism (CD) and 1 H NMR spectroscopic techniques. In their studies, the extraction of ribose from a polar protic solvent into an apolar aprotic solvent was even reported.…”
Section: Introductionmentioning
confidence: 99%
“…Resorcarene complexation has been reported with alkali metal cations, [3] alcohols, [4] various nitrogen compounds, [5] sugars, [6] and steroids. [7] Mass spectrometry (MS) with a soft ionization technique, such as electrospray ionization (ESI), [8] is challenging the more traditional methods, such as X-ray diffraction methods [9,10] and NMR spectroscopy, [3a, 4, 7a, 11, 12] in studies of hostguest complexation. ESI-MS has four benefits in the study of noncovalent complexes: stoichiometry, specificity, sensitivity, and speed.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Compound 5 was deprotected in THF with Bu 4 N F À and subsequently allowed to react with two equivalents of calix [4]arene 8. The reaction produced 2 (endo ± exo) [8] in 21 % yield, as the most abundant isomer (Scheme 1), the endo ± endo and exo ± exo isomers were isolated in 8 and 18 % yield, respectively. As previous studies in solution showed that steroids interact almost equally with all three isomers, [8] only the endo ± exo isomer was used for monolayer formation.…”
Section: Resultsmentioning
confidence: 99%
“…[5] Derivatized b-and gcyclodextrins have also been used to solubilize cholesterol in water [6] and as fluorescent receptor molecules for bile acids, respectively. [7] In our group, Higler et al [8] recently showed that molecular platform 3 is able to complex steroids in CDCl 3 . So far, recognition of steroid molecules with synthetic receptors has only been attempted in solution.…”
mentioning
confidence: 96%